Pemahaman Masyarakat Tentang Jual Beli Cengkeh Yang Masih Di Pohon (Ijon) Di Kecamatan Passi Barat Kabupaten Bolaang Mongondow - Syamsuddin Ak Antuli (Tasharruf: Journal Economics and Business of Islam, 2018)
The practice of buying and selling by using Ijon are widely practised in the villages such as pasi Barat when the cloves are still on trees.Based on this description, the writer tries to investigate on people understanding of buying and selling cloves which are still on trees (Ijon). This is field research with descriptive analyses methods that is qualitative research that will produce normative data acquired through direct interview on purposive sampling. Purposive sampling is selected due to the ability to represent the population. Furthermore, documentation technique is used to explore existing data related to research based on data collected and the analysis performed it can be concluded that people understanding especially cloves farmers on Ijon styles buying and selling is varied. According to researcher observation, the varied understanding are based on this issue is due to the low knowledge on religion. Most respondents cannot respond when asked about the Ijon.Keywords: Buying and Selling, Understanding and Ijon